Packaging and storage study on saluyot (Corchorus olitorius Linn.) powder - Najera, Teodora Amor Avellanosa; Galvez, Flor Crisanta F. (1995.)
The microbial stability of saluyot powder upon prolonged storage and the sorption behavior were determined as affected by blanching time and drying temperature. The products that were dried at a temperature of as low as 60°C an with moisture contents of 2.00% to 4,9%, were found still microbiologically stable after two months of storage at room temperature and humidity, using 0.025 mm polyethylene and aluminum laminate bags as packaging materials. Less microbiological growth was observed for samples processed at higher temperatures. Steep sorption isotherms and monolayer values in the range of 2.878 to 5.988% obtained for all the nine treatments suggest that the products were highly hygroscopic. It was found that the higher the drying temperature, the lower the moisture content, and the more hygroscopic the product was. Blanching time did not have any effect on the microbial growth and the sorption behavior of saluyot powder.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetable powder -- Storage